INSTITUTIONAL TRANSFORMATIONS: imagination, embodiment, and affect. - Celermajer, Danielle; Churcher, Millicent; Gatens, Moira (Angelaki: Journal of the Theoretical Humanities, 2019)
The article offers information on adopting of a broad understanding of institutions as embodied and organizing framework. Topics discussed include formal and informal institutions structure for social interactions by giving normative expectations and patterns of collective behavior; mentions the influence of embodiment and affect in structuring of individuals and groups to flourish in various social and material settings; and explores imaginative forms and social imaginaries.